Prinsip Transaksi Marketplace Digital dalam Al-Qur’an: Kajian Tafsir Tematik terhadap Ayat-Ayat Mu‘āmalah - Ely Zahrah; Abdul Syukkur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
online marketplace platforms that facilitate faster and more efficient economic transactions. However, the emergence of digital marketplaces also raises issues related to the legality of transactions, transparency, and ethical standards from an Islamic perspective. This study aims to analyze digital marketplace practices through a thematic interpretation (al-tafsīr al-mawḍū‘ī) of Qur’anic verses related to mu‘āmalah and to examine their relevance within the framework of maqāṣid al-syarī‘ah.This research employs a qualitative approach using library research methods. Primary sources include the Qur’an and classical as well as contemporary tafsir works, while secondary sources consist of books, journal articles, and previous studies related to digital marketplaces and Islamic economics. The study focuses on the analysis of QS. al-Baqarah: 275, QS. an-Nisā’: 29, and QS. al-Baqarah: 282.The findings indicate that digital marketplaces can be considered compatible with Islamic principles when they uphold lawful transactions, mutual consent, transparency, and clarity of contracts, while avoiding ribā, gharar, fraud, and deceptive practices. These principles are closely related to the objectives of maqāṣid al-syarī‘ah, particularly in protecting wealth (ḥifẓ al-māl) and preventing harm in economic transactions. Therefore, integrating Qur’anic ethical values into digital marketplace systems is essential for establishing fair, transparent, and sustainable digital commerce.